Orbital two-channel Kondo effect in epitaxial ferromagnetic L10-MnAl films - L. J. Zhu (Nature Portfolio, 2016)
In metals, electronic scattering from defects by the two-channel Kondo effect is expected to cause deviation from standard low temperature behaviour, however this effect has not been unambiguously shown. Here, the authors present evidence consistent with all transport signatures of the effect in ferromagnetic L10-MnAl films.